KONTRIBUSI PERGAULAN TEMAN SEBAYA, PENDIDIKAN ORANG TUA DAN FASILITAS BELAJAR TERHADAP MOTIVASI BELAJAR DI SMA NEGERI I SAMBI BOYOLALI - SUPANA, SUPANA (2011)
Education is one of the most strategic component in the formation of human resources quality. Many teachers in SMA I Sambi Boyolali who complained of low ability students. This is evident from the low student learning outcomes indicated by the value of daily tests, semester, or school final exams, but in the implementation process of learning in the classroom is usually the teacher gives assignments (strengthening) of continuous form of exercises. The low quality of learning can mean a lack of effective learning process. The purpose of this study to analyze and find out the contribution of peer interaction, parent education, and learning facilities are partially or simultaneously on student motivation in SMA Negeri 1 Sambi Boyolali. Location of the study in SMA Negeri 1 Sambi Boyolali with the entire student population numbered 250 people. The number of samples of 152 students based Krejcie table. Sampling technique using random sampling method. The independent variables are the association of peers, parents' education and learning facilities, while the dependent variable of motivation to learn. Collecting data using questionnaires and secondary data that exist in schools. Data analysis using the classic assumption test and multiple linear regression test. Results showed that (1) Variable peers to have significantly contributed to learning motivation variables of 27.8%. Correlation coefficient (r) of 0.528; significance p = 0.000 (<= 0.05). (2) parent education variables have significantly contributed to the variable of motivation to learn by 4.7%. Correlation coefficient (r) of 0.217: p = 0.007 (<= 0.05). (3) Variable-learning facilities have contributed to the variable of motivation to learn by 0.4% but the contribution was not significant. Correlation coefficient (r) equal to 0.065, p = .429 (<= 0.05). (4) Variable peers, parents' education and learning facilities together have contributed to the variable of motivation to learn at 29.2%. Determinant coefficient (r2) equal to 0.292, p = 0.000 (<= 0.05).The conclusion of this research is no contribution of peer group, parent education, and learning facilities simultaneously on student motivation in SMA Negeri 1 Sambi Boyolali as much as 29.2%.